Peran Bank DKI dalam pembiayaan infrastruktur di Jakarta: Tantangan dan dampak - najihah, wilda ainun (Maliki Interdisciplinary Journal, 2025)
Bank DKI’s role in infrastructure financing in Jakarta, which is one of the largest cities in Southeast Asia. With high investment needs in the development of transportation infrastructure, health, education, and public utilities infrastructure development, Bank DKI serves as a strategic financial institution that bridges the needs of local government with the availability of funds. availability of funds. Despite facing various challenges such as limited financial resources and competition from national and international banks, Bank DKI remains committed to supporting infrastructure projects that have a major impact on the community, including the construction of infrastructure projects that have a major impact on the community, including the construction of toll roads, mass mass transportation system, and affordable housing. The impact of Bank DKI’s infrastructure financing by Bank DKI is significant in improving the quality of life of Jakartans and regional economic growth. The projects financed projects not only create jobs but also improve accessibility and efficiency of transportation. and transportation efficiency. However, challenges such as economic fluctuations and the need to ensure the financial sustainability of projects remain a major concern. a major concern. This research aims to provide new insights for stakeholders in designing more effective and sustainable financing policies, as well as strengthening Bank DKI’s role as an effective and sustainable financing policies, as well as strengthening Bank DKI’s role as a strategic partner in infrastructure development in Jakarta